Historical and architectural heritage of the CER: Hengdaohezi - Bazilevich, Evgeny; Tceluiko, Dmitry (project baikal, 2026)
The article publishes the materials and results of a study conducted by the authors with the support of a grant from the Russian Science Foundation “Methods of integrating historical development zones and preserving cultural heritage sites in the context of the development of modern cities in Northeast China.” The authors present the data obtained during the historical and architectural study of the township of Hengdaohezi located on the eastern section of the Chinese-Eastern Railway (CER), which are related to the formation of its planning structure and architectural landscape. The zones of historically valuable development have been identified, and its individual objects relevant for the development of tourism have been considered